ARTICLE REVIEW: THE IMPORTANCE OF THE ENVIRONMENTAL MANAGEMENT SYSTEM: FOR SMALL BUSINESSES - Cicero Silva, Luciano; de Oliveira Francklin, Bruna; Matteus Oliveira Souza, Igor; Cristina de Oliveira Bagnarelli, Jéssica; Eduarda de Lima Ferreira, Maria (Revista Gênero e Interdisciplinaridade, 2023)
This review presents the article “The Importance of the Environmental Management System: for Small Businesses”, written by the authors Bruno de Sousa Carvalho Tavares, who holds a master’s degree in Bioengineering, and Érica dos Santos Guedes, a graduate student in Environmental Engineering at Anhanguera College, published by the Brazilian Journal of Teaching and Learning. The article presented by the author seeks to demonstrate the importance of caring for the environment in small businesses. From the notes revealed in the article, I understand that the environmental management system is important for social life and to avoid shortages of raw materials.